The mechanism of genetic predisposition in congenital dislocation of the hip. - Czeizel, A (1975)
The important role of polygenic acetabular configuration and monogenic joint laxity has again been proved in the aetiology of congenital dislocation of the hip. According to the findings reported these two genetic predispositions seem to be unrelated. The time of diagnosis in accetabular dysplasia type and joint laxity type did not differ, thus the neonatal and late-diagnosed cases do not seem to be two clear-cut entities.